Pattern of asymptomatic sexually transmitted infections in women undergoing hysterosalpingography for infertility evaluation in Ibadan Nigeria (2013)
"The roles of gonorrhea and non-gonococcal urethritis due to Chlamydia trachomatis in the etiology of infertility due to tubal occlusion have been established by various studies. Hysterosalphingography WSG) is done to investigate tubal patency. This study was aimed at finding the prevalence of asymptomatic sexually transmitted infections (STIs) in women being investigated for infertility in a tertiary institution.Methods: This was a cross-sectional study of asymptomatic infertile women referred for pre-HSG screening. Detailed medical history, Endocervical and high vaginal swabs were collected to establish diagnosis of STIs following clinical examination and informed consent. These specimens were evaluated microscopically for Chlamydia trachomatis and bacterial vaginosis. Endocervical secretions were Gram-stained for intracellular Gram - Negative diplococci and suspected isolates were confirmed as Neisseriagonorrhoeae by standard laboratory methods. Results: There were 250 participants with a mean age of 34.6 years (SD = 5.4, range = 25 -49). The mean age of sexual debut of participants was 21.5 years (SD = 4.3). Fifty-six (22.5%) of the women engaged in oral sex while 53 (2 1.2 %) shared their spouses with other sexual partners. 1 7.7% had previous PID, 43.1% of them has vaginal discharge syndrome. The commonest ST1 was Vulvo- vaginal candidiasis (24.4%) and others were bacterial vaginosis (18.4%), Chlamydia cervicitis ( 17.6% ), trichomoniasis (11.2% ), and gonomhea ( 2.4 % ). Conclusion: The procedure of HSG is invasive and asymptomatic infections in the cervix can be dislodged and propagated by injectionof contrast to the fallopian tubes thus causing tubal blockage. Routine Per -HSG screening for occult STIs is encouraged to avoid iatrogenic Pelvic Inflammatoty Disease "